Institution initiatives and support related to faculty development of open educational resources and alternative textbooks. (2nd January 2020) - McGowan, Veronica
ABSTRACT: Evidence exists that American institutions of higher education are well-entrenched in the consideration of mechanisms for supporting the implementation of Open Educational Resources (OER) and alternative textbooks. Literature reveals that developing and implementing OER is a significant undertaking in terms of time and human resources. This study deploys content analysis of a sample of United States regionally based higher education institutional websites to determine the current state of institutional support mechanisms to implementers just embarking on the OER journey. Findings reveal that institutions have made strides in the development of faculty mini-grants and stipends with guidelines, proposal checklists, and weighting mechanisms to inform decision making. However, due to widespread language across the stratified sample emphasising award pool and individual limits, it is clear that OER funding is still seeking wider support as a permanent funded resource. Sponsorship of institutional OER initiatives seems split between institutional library functions and teaching and learning centres. Other issues, such as ownership and licensing, are significantly underdeveloped in field implementation or fall in a large continuum of practices. Recommendations of shared responsibility and use of data driven initiatives are provided that may improve institutional support of faculty OER adoption, adaption and creation.